ANALISIS PENERAPAN PERATURAN PEMERINTAH NO. 46 TAHUN 2013 TERHADAP TINGKAT PENERIMAAN PAJAK DI KPP PRATAMA BADUNG SELATAN - Natalia, Amanda; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 19 No 3 (2017), 2017)
The Government is trying to optimize the tax revenue through the UMKM sector by publishing new rules, namely Goverment Regulation No. 46 year 2013 on June 13, 2013. The purpose of this research is to know difference of tax the tax payer acceptance level corporate and personal 2013 in the KPP Pratama Badung Selatan before and after the application of PPh pasal 4 ( 2 ) final . The sample in this research is t ax payer's personal and corporate active who qualify imposed Government Regulation No. 4 6 2013 for t ax payers is 966 t ax payers, while for the personal is 1232 t ax payers with a purposive sample as asampling method. The results of the the test of Wilcoxon Signed Rank Test found that there is a difference s in the level of tax revenue corporate and personal tax payers before and after application of the Government Regulation No. 4 6 2013 in KPP Badung Selatan.
Keywords: Government Regulation No. 46 year 2013, UMKM, KPP Pratama Badung Selatan